Introducing the Slave Next Door - Birks, Jen; Gardner, Alison (Anti-Trafficking Review, 2019)
Past studies have indicated that the British public consider human trafficking to be remote from their personal experiences. However, an increase in local press reporting, alongside the emergence of locally co-ordinated anti-modern slavery campaigns, is starting to encourage communities to recognise the potential for modern slavery and human trafficking to exist in their own localities. In this article, we examine how local media and campaigns may be influencing public perceptions of modern slavery and human trafficking. We draw upon a content analysis of local newspapers to review how reports represent cases of modern slavery, and use focus group discussions to understand how local coverage modifies—and sometimes reinforces—existing views. We find that, whilst our participants were often surprised to learn that cases of modern slavery and human trafficking had been identified in their area, other stereotypical associations remained entrenched, such as a presumed connection between modern slavery and irregular migration. We also noted a reluctance to report potential cases, especially from those most sympathetic to potential victims, linked to concerns about adequacy of support for survivors and negative consequences relating to immigration. These concerns suggest that the UK’s ‘hostile environment’ to migrants may be undermining the effectiveness of ‘spot the signs’ campaigns, by discouraging individuals from reporting.